Avaliação dos indicadores do uso de medicamento na atenção pediátrica das unidades básicas de saúde, em Feira de Santana, Bahia - Almeida, Carolina Carvalho (2015)
This research consisted of an epidemiological, descriptive and retrospective study that aimed to evaluate the profile of drug prescriptions for pediatric patients in primary care in Feira de Santana, Bahia, from August 2012 to July 2013, using the drug use indicators recommended by the World Health Organization. The source of data for this study was the second copy of all prescriptions elaborated by physicians in pediatric consultations and retained in basic health units. At the same time we carried out a systematic review of the literature, which consisted of searching the databases MEDLINE, LILACS and SciELO, in January 2014, at original studies that used as methodology the drug use indicators in pediatric patients, sample or population, published in English, Portuguese or Spanish, at primary care services and without time restriction. This systematic review afforded studies to be compared with the results obtained. Four studies were included in none of these was obtained twelve basic indicators. Facility indicators could not be compared because only one of the four studies evaluated. Regarding the profile of prescriptions, it was found that the average number of drugs was 1.9, and 71.4% were prescribed by generic name, 81.6% were present in the Brazilian National List of Essential Medicines 2012 and 76,4% were dispensed. In 32.7% of prescriptions had at least one antibiotic, and 0.2% at least one injectable drug. It was confirmed the shortage of drug use studies in pediatrics with the methodology used and evaluated positively the values found for the drug use indicators in Feira de Santana, but, considering importance in improving the service offered, it is expected that the prescription by generic name, essential drugs and the dispensation of prescription drugs is even closer to 100%; and that antibiotics can be prescribed rationally.